Bactericidal Activity of Silver Nanoparticles on Oral Biofilms Related to Patients with and without Periodontal Disease - Hernández-Venegas, Perla Alejandra; Martínez-Martínez, Rita Elizabeth; Zaragoza-Contreras, Erasto Armando; Domínguez-Pérez, Rubén Abraham; Reyes-López, Simón Yobanny; Donohue-Cornejo, Alejandro; Cuevas-González, Juan Carlos; Molina-Frechero, Nelly; Espinosa-Cristóbal, León Francisco (Journal of functional biomaterials, 2023)
Background and Objectives: Periodontal disease (PD) is a multifactorial oral disease regularly caused by bacterial biofilms. Silver nanoparticles (AgNP) have offered good antimicrobial activity; moreover, there is no available scientific information related to their antimicrobial effects in biofilms from patients with PD. This study reports the bactericidal activity of AgNP against oral biofilms related to PD. Materials and Methods: AgNP of two average particle sizes were prepared and characterized. Sixty biofilms were collected from patients with (30 subjects) and without PD (30 subjects). Minimal inhibitory concentrations of AgNP were calculated and the distribution of bacterial species was defined by polymerase chain reaction. Results: Well-dispersed sizes of AgNP were obtained (5.4 ± 1.3 and 17.5 ± 3.4 nm) with an adequate electrical stability (−38.2 ± 5.8 and −32.6 ± 5.4 mV, respectively). AgNP showed antimicrobial activities for all oral samples; however, the smaller AgNP had significantly the most increased bactericidal effects (71.7 ± 39.1 µg/mL). The most resistant bacteria were found in biofilms from PD subjects (p < 0.05). P. gingivalis, T. denticola, and T. forsythia were present in all PD biofilms (100%). Conclusions: The AgNP showed efficient bactericidal properties as an alternative therapy for the control or progression of PD.